Pediatric Blunt Thoracic Trauma - Alemayehu, Hanna; Aguayo, Pablo (Journal of Pediatric Intensive Care, 2015)
Thoracic injury in children deserves special attention because, although it accounts for less than 10% of traumatic injuries in children, there is a significant associated morbidity and mortality. This review discusses the anatomic and physiologic factors resulting in such injury severity with blunt thoracic trauma in children. Specific organ injuries, including most common chest wall injuries, hemo- and pneumothoraces, and pulmonary parenchymal injuries, are discussed, encompassing epidemiology, presentation, diagnosis, and management. Rare injuries including tracheobronchial tree injuries, cardiovascular injuries, esophageal injuries, and diaphragmatic injuries are also briefly discussed.
Keywords: thoracic trauma; chest trauma; pulmonary injury; children